UNDERSTANDING THE JOURNEY: NARRATIVES OF SECONDARY SCHOOL PRINCIPALS ON TRANSITIONING TO AN AI-DRIVEN EDUCATIONAL SYSTEM - Angelito M. Ebora (Jurnal Riset Multidisiplin Edukasi, 2026)
This qualitative study explores school principals' perceptions of AI integration in secondary public schools in SDO Pangasinan II through five structured open-ended prompts (SOPs), yielding four recurrent themes across visionary ideals, hopes, observed experiences, challenges, and essential supports. Principals envision AI-driven schools as transformative environments enabling personalized learning, automated administration, data-informed leadership, and ethical human-centered education, while expressing hopes for efficiency, inclusivity, and innovation alongside fears of job displacement, dehumanization, data privacy breaches, and overreliance. Current experiences highlight enhanced teaching efficiency and student engagement tempered by concerns over academic integrity and adjustment anxieties, with major barriers including inadequate infrastructure, training gaps, ethical risks, budget limitations, and policy voids. Findings highlight a paradox in readiness regarding AI in education, where strong enthusiasm for its potential exists alongside significant infrastructural gaps and ethical concerns. These elements call for ongoing professional development, substantial technological upgrades, supportive Department of Education (DepEd) policy frameworks, and partnerships among various stakeholders to ensure equitable implementation. Insights derived from secondary school principals resonate with global trends, promoting a balanced and future-focused approach to AI, particularly in resource-limited settings. This aims to formulate strategic plans that tackle existing challenges and facilitate equitable and accessible AI integration in public secondary education.